Penilaian efektivitas Lapangan Lumintang sebagai ruang terbuka publik di Kota Denpasar - Dewi, I Gusti Ayu Feby Purnami; Semarajaya, Cokorda Gede Alit; Mayun, Ida Ayu (Jurnal Arsitektur Lansekap; Vol.7, No.1, April 2021DO - 10.24843/JAL.2021.v07.i01.p04, 2021)
Lumintang Field is one of the artificial landscapes in the form of public open space with its main function as a ceremonial field. At present, the field also has an additional function as a place for sports, recreations and educations, its evidenced by the construction of various facilities to support community activities. Although it has been improved, this field still has problems, such as the number of visitors stepping on low plants when entering the field, so that access to the field that is not functioning properly and the absence of a parking lot makes visitors park carelessly. The purpose of this study is to assess the effectiveness of Lumintang Field as a public open space in Denpasar City. The method used is a survey method with data collection techniques are observation, questionnaire distribution, interviews, and literature study, with data analysis such as Lumintang Field facilities analysis and analysis of public space effectiveness. The results revealed that the existence of Lumintang Field as a public open space in Denpasar City was quite effective with a value of 2.0. The participation of visitors is needed to participate in maintaining the cleanliness and preservation of Lumintang Field, and the management can make the results of the research as a reference in the future improvement of the field area.